Benzodiazepine-resistant epilepsy: unraveling molecular mechanisms and developing multimodal therapeutic strategies - Huang, Yanqiu; Zhang, Yangfan; Liang, Yi (Frontiers in Neurology, 2025)
Epilepsy is one of the most common nervous system diseases, which is characterized by recurrent seizures caused by abnormal neuronal discharges in the brain. Drug-resistant epilepsy (DRE) brings great challenges to clinical treatment. Benzodiazepines (BZDs), as the first-line treatment for acute seizures and Status Epilepticus (SE), are widely used because of their potent inhibitory neuromodulation by regulating γ-aminobutyric acid-A(GABAA) receptors. However, long-term use of BZDs may induce drug resistance, leading to a significant decrease in efficacy and increasing the difficulty of treatment. This study begins with the definition of BZDs-resistant epilepsy. It explores the underlying resistance mechanisms, including the down-regulation, decreased activity, and structural changes of GABAA receptors, synapse and neural network remodeling, genetic variation in drug metabolism, and the effects of drug efflux mechanisms. In addition, combined with clinical practice and research progress, this study evaluates the effectiveness and potential of drug combination therapies, personalized treatments, and new treatment methods, highlighting the advantages of simultaneous multi-drug therapy in controlling drug-resistant epilepsy. Further research on the mechanisms of BZDs resistance and optimization of treatment strategies can not only improve the therapeutic effect of drug-resistant epilepsy but also provide a scientific basis for the development of antiepileptic drugs in the future.